High-performance sulfide solid electrolyte material and preparation method thereof and application in all-solid-state batteries

By introducing Cu and Br elements into the sulfide solid electrolyte, a high-performance electrolyte composed of Li6-2xCuxPS5-xBr1+x chemical composition was prepared, which solved the air instability and lithium instability of the sulfide electrolyte and achieved higher The ionic conductivity and cycling stability improve the safety and performance of all-solid-state lithium batteries.

CN115377483BActive Publication Date: 2024-12-17ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210966091.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-12
Publication Date
2024-12-17
Estimated Expiration
2042-08-12

AI Technical Summary

Technical Problem

Sulfide solid electrolytes have problems with air instability and lithium in large-scale applications, resulting in increased safety and manufacturing costs, hindering their commercialization process.

Method used

Using the chemical composition of Li6-2xCuxPS5-xBr1+x, high-performance sulfide solid electrolyte is prepared through ball milling, tableting, heat treatment and other steps, Cu elements and Br elements are introduced to improve air stability and lithium stability, and superion conductor materials are formed. .

Benefits of technology

It significantly improves the air stability and lithium stability of sulfide solid electrolyte, extends the lithium cycle stability time, inhibits the growth of lithium dendrites, and enhances the cycle stability and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115377483B_ABST
    Figure CN115377483B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of solid-state batteries, and discloses a high-performance sulfide solid electrolyte material and a preparation method thereof and an application in all-solid-state batteries. The present invention provides a superionic conductor sulfide solid electrolyte with high air stability and high lithium stability, and its chemical composition is Li 6‑2x Cu x PS 5‑x Br 1+x , wherein x is 0 to 1; based on the theory of soft and hard acid and base, the present invention is to + Ions are doped into the solid electrolyte to improve the binding property with sulfur, thereby improving the air stability of the solid electrolyte. ‑ The introduction of ions improves the ionic conductivity of the solid electrolyte on the one hand, and also improves the lithium stability of the solid electrolyte on the other hand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to the synthesis of a superionic conductor solid electrolyte material with high air stability and high lithium stability and its application in solid-state batteries. Background Art

[0002] Lithium batteries have the advantages of high energy density, long service life, and excellent cycle performance. They have been widely used in daily life and have become the first choice for rechargeable power sources for portable electronic products and electric vehicles today. However, with the frequent reports of fire and explosion of traditional lithium-ion batteries, people are increasingly concerned about the safety of lithium-ion batteries. Recent studies have shown that replacing liquid organic electrolytes with solid electrolytes to assemble all-solid-state lithium batteries can effectively solve potential safety issues. Solid electrolytes, as an important component of all-solid-state lithium batteries, have received extensive attention. In the past few decades, various solid electrolytes containing polymers, oxides, and sulfides have been studied in detail. Among them, sulfide solid electrolytes have ultrahigh ionic conductivity comparable to that of organic liquid electrolytes and are considered to be the most promising candidate solid electrolytes. In addition, sulfide solid electrolytes have intrinsic soft mechanical properties, which facilitates intimate interfacial contact after a simple cold pressing process.

[0003] However, there are still some problems in the large-scale application of sulfide solid electrolytes. On the one hand, due to the relatively narrow electrochemical stability window of sulfide electrolytes, they are severely incompatible with the lithium anode. Interfacial side reactions can lead to uneven lithium deposition, resulting in lithium dendrite growth, which eventually pierces the sulfide electrolyte. On the other hand, because sulfide electrolytes are very hygroscopic. Even a small amount of moisture can cause the degradation of sulfide electrolytes and release toxic H2S gas. Therefore, the synthesis, transportation and storage of sulfide electrolytes must be strictly carried out under the protection of vacuum or inert gas, which will increase the manufacturing cost and hinder the commercialization of sulfide electrolytes. Therefore, on the basis of maintaining the high ionic conductivity of sulfide electrolytes, the development of a new sulfide solid electrolyte with high air stability and lithium stability is a prerequisite for the realization of all-solid-state lithium batteries. Summary of the invention

[0004] The present invention provides a high-performance sulfide solid electrolyte material and a preparation method thereof and application in an all-solid-state battery. The sulfide solid electrolyte provided by the present invention has high ion conductivity and air stability as well as lithium stability.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] A high-performance sulfide solid electrolyte material, namely a sulfide solid electrolyte with high air stability and lithium stability, whose chemical composition is Li 6-2x Cu x PS 5-x Br 1+x , where 0 <x≤1。

[0007] The method for preparing the sulfide solid electrolyte with high air stability and lithium stability comprises the following steps:

[0008] (1) weighing Li2S, P2S5, LiBr, and CuBr in appropriate proportions and mixing them by ball milling to obtain an initial solid electrolyte material;

[0009] (2) The initial solid electrolyte material obtained in step (1) is pressed into a sheet and maintained under pressure for a period of time to obtain a compacted electrolyte sheet, which is then placed in a quartz test tube, sealed, and then heat treated. The obtained electrolyte sheet is then ground into powder to obtain a superionic conductor sulfide solid electrolyte material.

[0010] The chemical composition of the superionic conductor sulfide solid electrolyte with high air stability and high lithium stability provided by the present invention is Li 6-2x Cu x PS 5-x Br 1+x , wherein x is preferably 0 to 1, more preferably 0.1 to 0.8, and more preferably 0.2 to 0.6; in the present invention, according to the hard-soft acid-base theory, the combination of the Cu element and the S element is more stable, which can effectively stabilize the electrolyte structure and inhibit the generation of toxic H2S, thereby improving the air stability of the sulfide solid electrolyte. In addition, the introduction of the Br element can generate new lithium ion migration channels, improve the ionic conductivity of the electrolyte, and the high bromine content can further stabilize the interface with the lithium metal, thereby improving the stability to lithium.

[0011] In step (1), during the ball milling process, the molar ratio of Li2S, LiBr, P2S5 and CuBr is 3-5:2:1:0-2, preferably 3.1-4.9:2:1:0.1-1.9, and more preferably 3.2-4.8:2:1:0.2-1.8.

[0012] In step (1), the rotation speed of the ball mill is 500 to 1000 rpm, preferably 600 to 800 rpm, and the time of the ball mill is 10 to 30 hours, preferably 15 to 24 hours.

[0013] In step (1), the ball milling is carried out in an inert gas atmosphere, and the inert gas is preferably any one of helium, argon and neon, and more preferably carried out in an argon atmosphere.

[0014] In step (2), the pressure used for the electrolyte tableting is 300-600 MPa, more preferably 350-450 MPa, and the pressure holding time is 5-20 minutes, more preferably 6-12 minutes.

[0015] In step (2), the heat treatment temperature is 400-600° C., preferably 450-550° C. The heat treatment time is 2-20 hours, preferably 5-15 hours.

[0016] The application of the sulfide solid electrolyte material with high air stability and lithium stability in the preparation of all-solid-state lithium batteries. The application specifically includes:

[0017] The positive electrode sublimated sulfur and vapor-grown carbon fiber (VGCF) and high ionic conductivity sulfide solid electrolyte material are weighed in a mass ratio of 7:1:2 and placed in a ball mill for mechanical milling for 1-10 hours, preferably 2-6 hours, with a rotation speed of 100-600 rpm, preferably 150-300 rpm, to obtain a composite positive electrode powder;

[0018] The solid electrolyte and the composite positive electrode are placed in a customized mold in turn, and maintained at a pressure of 200-600 MPa for 2-20 minutes, preferably at a pressure of 250-400 MPa for 5-15 minutes. Then, the lithium sheet is placed on the other side of the electrolyte, and then on the stainless steel current collector on both sides, and a pressure of 20-100 MPa is applied. The pressure is maintained for 1-15 minutes, preferably at a pressure of 25-60 MPa for 2-10 minutes, and the solid-state lithium battery is obtained by compacting.

[0019] The present invention provides a superionic conductor solid electrolyte material with high air stability and high lithium stability. Its chemical composition is Li 6-2x Cu x PS 5-x Br 1+x , wherein x is 0 to 1. Based on the theory of soft and hard acid and base, the present invention is to + Ions are doped into sulfide solid electrolytes to improve the binding properties with sulfur, thereby improving the air stability of the solid electrolyte. - The introduction of ions improves the ionic conductivity of the solid electrolyte on the one hand, and also improves the lithium stability of the solid electrolyte on the other hand.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] The sulfide solid electrolyte material provided by the present invention is used in an all-solid-state battery. Since copper has a stronger electronegativity, the electrochemical stability of the electrolyte is enhanced. Even if the electrolyte decomposes, the synthetic electrolyte has a higher bromine content and thus has a longer lithium cycle stability time.

[0022] The all-solid-state battery assembled with the solid electrolyte material provided by the present invention has better lithium stability and can effectively inhibit the growth of lithium dendrites, thereby helping to improve the cycle stability and safety performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the highly air-stable nanocrystalline sulfide solid electrolyte prepared in Example 1;

[0024] Figure 2 Graphs showing ionic conductivity of electrolytes prepared in Example 1 and Comparative Example 1;

[0025] Figure 3 It is a curve diagram of the change of H2S content in the air of the electrolyte prepared in Example 1 and Comparative Example 1 over time;

[0026] Figure 4 Graphs showing lithium cyclic deposition and stripping of lithium / solid electrolyte / lithium symmetric cells assembled using the sulfide solid electrolytes prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0027] In order to further illustrate the present invention, a sulfide solid electrolyte and solid-state battery with high air stability and lithium stability and a preparation method thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0028] Example 1

[0029] Preparation of highly air-stable and lithium-stable sulfide solid electrolytes:

[0030] Li2S, LiBr, P2S5 and CuBr were mixed in a molar ratio of 4.4:2:1:0.6, and placed in a zirconia grinding jar under argon protection. The ball milling speed was 600rpm and the ball milling time was 20 hours to obtain the initial sulfide solid electrolyte powder. The initial sulfide solid electrolyte powder was pressed into an electrolyte sheet at a pressure of 400MPa for 10 minutes, and then the electrolyte sheet was sealed in a quartz tube and placed in a muffle furnace for heat treatment to promote electrolyte crystallization. The heat treatment temperature was 500 degrees Celsius and the heat preservation time was 10 hours. The sintered electrolyte sheet was ground into powder to obtain highly crystallized sulfide solid electrolyte powder. Its chemical composition is Li 5.4 Cu 0.3 PS 4.7 Br 1.3 ;

[0031] Preparation of solid-state batteries:

[0032] The positive electrode sublimated sulfur and vapor-grown carbon fiber (VGCF) and high ionic conductivity sulfide solid electrolyte material were weighed in a mass ratio of 7:1:2 and placed in a ball mill for mechanical milling at a ball mill speed of 200 rpm for 2 hours to obtain a composite positive electrode powder;

[0033] The solid electrolyte and composite positive electrode were placed in a customized mold in turn, maintained at a pressure of 400 MPa for 10 minutes, and then the lithium sheet was placed on the other side of the electrolyte, and then on the stainless steel current collectors on both sides, and a pressure of 20 MPa was applied and maintained for 1 minute to obtain a solid-state lithium battery.

[0034] Example 2

[0035] Preparation of highly air-stable and lithium-stable sulfide solid electrolytes:

[0036] Li2S, LiBr, P2S5 and CuBr were mixed in a molar ratio of 3.8:2:1:1.2, and placed in a zirconia grinding jar under argon protection. The ball milling speed was 600rpm and the ball milling time was 20 hours to obtain the initial sulfide solid electrolyte powder. The initial sulfide solid electrolyte powder was pressed into an electrolyte sheet at a pressure of 400MPa for 10 minutes, and then the electrolyte sheet was sealed in a quartz tube and placed in a muffle furnace for heat treatment to promote electrolyte crystallization. The heat treatment temperature was 500 degrees Celsius and the heat preservation time was 10 minutes. The sintered electrolyte sheet was ground into powder to obtain highly crystallized sulfide solid electrolyte powder. Its chemical composition is Li 4.8 Cu 0.6 PS 4.4 Br 1.6 ;

[0037] Preparation of solid-state batteries:

[0038] The cathode S sublimated sulfur and vapor-grown carbon fiber (VGCF) and high ionic conductivity sulfide solid electrolyte material were weighed in a mass ratio of 7:1:2 and placed in a ball mill for mechanical ball milling at a ball mill speed of 200 rpm for 2 minutes to obtain a composite cathode powder.

[0039] The solid electrolyte and composite positive electrode were placed in a customized mold in turn, maintained at a pressure of 400 MPa for 10 minutes, and then the lithium sheet was placed on the other side of the electrolyte, and then on the stainless steel current collectors on both sides, and a pressure of 20 MPa was applied and maintained for 1 minute to obtain a solid-state lithium battery.

[0040] Example 3

[0041] Preparation of highly air-stable and lithium-stable sulfide solid electrolytes:

[0042] Li2S, LiBr, P2S5 and CuBr were mixed in a molar ratio of 3:2:1:2, and placed in a zirconia grinding jar under argon protection. The ball milling speed was 600rpm and the ball milling time was 20 hours to obtain the initial sulfide solid electrolyte powder. The initial sulfide solid electrolyte powder was pressed into an electrolyte sheet at a pressure of 400MPa for 10 minutes, and then the electrolyte sheet was sealed in a quartz tube and placed in a muffle furnace for heat treatment to promote electrolyte crystallization. The heat treatment temperature was 500 degrees Celsius and the heat preservation time was 10 hours. The sintered electrolyte sheet was ground into powder to obtain highly crystallized sulfide solid electrolyte powder. Its chemical composition is Li4CuPS4Br2;

[0043] Preparation of solid-state batteries:

[0044] The cathode S sublimated sulfur and vapor-grown carbon fiber (VGCF) and high ionic conductivity sulfide solid electrolyte material were weighed in a mass ratio of 7:1:2 and placed in a ball mill for mechanical milling at a ball mill speed of 200 rpm for 2 hours to obtain a composite cathode powder.

[0045] The solid electrolyte and composite positive electrode were placed in a customized mold in turn, maintained at a pressure of 400 MPa for 10 minutes, and then the lithium sheet was placed on the other side of the electrolyte, and then on the stainless steel current collectors on both sides, and a pressure of 20 MPa was applied and maintained for 1 minute to obtain a solid-state lithium battery.

[0046] Comparative Example 1

[0047] A solid electrolyte and a solid-state battery were prepared according to the method of Example 1, wherein CuBr was not added to the solid electrolyte, and Li2S, LiBr and P2S5 were mixed in a molar ratio of 5:2:1, and the chemical composition was Li6PS5Br.

[0048] Comparative Example 2

[0049] A solid electrolyte and a solid-state battery were prepared according to the method of Example 1, wherein the crystallization temperature of the heat-treated electrolyte was set to 700° C., and the other conditions remained unchanged.

[0050] Comparative Example 3

[0051] A solid electrolyte and a solid-state battery were prepared according to the method of Example 1, wherein the electrolyte powder obtained by ball milling was directly used without heat treatment for electrolyte crystallization.

[0052] Performance Testing

[0053] The sulfide solid electrolyte with high air stability and lithium stability obtained in Example 1 was subjected to SEM detection, and the test results are as follows: Figure 1 As shown. Figure 1It can be seen that the high air-stability nanocrystalline sulfide solid electrolyte provided by the present invention is irregular particles with a size of about 1 to 10 μm.

[0054] like Figure 2 As shown, after adding an appropriate amount of CuBr, the ionic conductivity of the solid electrolyte can be increased.

[0055] like Figure 3 As shown, after the introduction of CuBr into the electrolyte, the amount of H2S produced when the electrolyte is placed in the air is significantly reduced, indicating that CuBr improves the air stability of the electrolyte.

[0056] like Figure 4 As shown, the original Li6PS5Br assembled lithium symmetric battery short-circuited after 67 hours, but after adding CuBr, the electrolyte could be stably cycled for 1000 hours, indicating that the electrolyte has good stability to lithium and can be used in solid-state batteries.

[0057] The solid-state batteries obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to constant current charge and discharge tests, under the following test conditions: charge and discharge voltage range of 1.5 to 3.0 V, charge and discharge rate of 0.1 C, test temperature of 25° C., and 200 cycles. The test results are shown in Table 1.

[0058] Table 1 Cyclic stability test results of solid-state batteries obtained from Examples 1 to 3 and Comparative Examples 1 to 3

[0059] Capacity retention rate Capacity retention rate Example 1 98% Comparative Example 1 51% Example 2 95% Comparative Example 2 65% Example 3 90% Comparative Example 3 73%

[0060] It can be seen from Table 1 that the solid-state battery assembled using the high air stability and lithium stability sulfide solid electrolyte provided by the present invention shows excellent cyclability. At a rate of 0.1C, after 200 cycles, the capacity retention rate can reach more than 90%. From the results of Comparative Example 1, without adding any CuBr dopant, the solid-state battery assembled with the obtained electrolyte has poor cyclic stability. After 200 cycles, the capacity retention rate is only 51%. From the results of Comparative Example 2, it can be seen that inappropriate heat treatment temperature will also lead to reduced electrolyte performance. From the results of Comparative Example 3, it can be seen that if the ball-milled initial electrolyte powder is not heat-treated and crystallized, the electrolyte performance will also deteriorate.

[0061] In summary, the present invention introduces CuBr dopant into the sulfide solid electrolyte. Based on the theory of hard and soft acid-base, soft acid copper tends to combine with soft base sulfur rather than hard base oxygen element, thereby improving the binding stability with sulfur and thus improving the air stability of the sulfide solid electrolyte. The introduced bromine element introduces new lithium ion diffusion channels and increases the ionic conductivity of the electrolyte. On the other hand, the high bromine content can improve the lithium stability of the electrolyte.

[0062] Applying the air-stable and lithium-stable sulfide solid electrolyte provided by the present invention to solid-state batteries can effectively inhibit the growth of lithium dendrites and improve the cycle stability of solid-state batteries.

[0063] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-performance sulfide solid electrolyte material, comprising the following steps: (1) weighing Li2S, P2S5, LiBr, and CuBr in appropriate proportions and mixing them by ball milling to obtain an initial solid electrolyte material; (2) the initial solid electrolyte material obtained in step (1) is pressed and maintained for a period of time to obtain a compacted electrolyte sheet, which is then loaded into a reactor, sealed and heat treated, and then the obtained electrolyte sheet is ground into powder to obtain a high-performance sulfide solid electrolyte material; The chemical composition of the high performance sulfide solid electrolyte material is Li 6-2x Cu x PS 5-x Br 1+x , where 0 <x≤1。 2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of Li2S, LiBr, P2S5 and CuBr is 3~5:2:1:0~2.

3. The preparation method according to claim 1, characterized in that: In step (1), the ball milling speed is 500-1000 rpm, and the ball milling time is 10-30 hours; The ball milling was performed in an argon atmosphere.

4. The preparation method according to claim 1, characterized in that: In step (2), the tabletting pressure is 300-600 MPa, and the holding time is 5-20 minutes.

5. The preparation method according to claim 1, characterized in that: In step (2), the heat treatment temperature is 400-600° C., and the heat treatment time is 2-20 hours.

6. Use of the high-performance sulfide solid electrolyte material prepared by the preparation method according to any one of claims 1 to 5 in the preparation of an all-solid-state lithium battery.

7. The use according to claim 6, characterized in that: Specifically include: The positive electrode, the vapor-grown carbon fiber and the high-performance sulfide solid electrolyte material are placed in a ball mill for mechanical ball milling for 1-10 hours at a speed of 100-600 rpm to obtain a composite positive electrode powder; The solid electrolyte and composite positive electrode powder are placed in a customized mold in turn, maintained at a pressure of 200~600 MPa for 2~20 minutes, and then the lithium sheet is placed. Then, stainless steel current collectors are placed on both sides and a pressure of 20~100 MPa is applied. The pressure is maintained for 1~15 minutes and compacted to obtain a solid-state lithium battery.

8. The use according to claim 7, characterized in that: The mass ratio of the positive electrode, vapor-grown carbon fiber and high-performance sulfide solid electrolyte material is 6-8: 0.8-1.2: 1.5-2.5.

Citation Information

Patent Citations

  • Positive electrode mix

    CN104380508A